Cyclic Behavior of Steel Moment-Resisting Connections Reinforced by Alternative Column Stiffener Details I - Lee, Daeyong; Cotton, Sean C.; Hajjar, Jerome F.; Dexter, Robert J.; Ye, Yanqun (Engineering Journal, 2005)
Experimental and corroborating computational research was performed to reassess the design and detailing of column reinforcement (in other words, continuity plates and doubler plates) according to U.S. specifications for both seismic and non-seismic design and to explore economical alternative stiffener details. The performance of six full-scale girder-to-column cruciform specimens that use the Welded Unreinforced Flange-Welded Web (WUF-W) connection detail was evaluated. The effects on the cyclic behavior of three different doubler plate details, including a back-beveled fillet-welded detail, a square-cut fillet-welded detail, and a box (offset) detail, were investigated. In addition, the performance of a continuity plate approximately half the thickness of the girder flange fillet-welded to both the column flanges and doubler plates was investigated. Current local flange bending and local web yielding design criteria were evaluated and the applicability of the suggested alternative column stiffener details was verified. A companion paper outlines findings with respect to panel zone behavior and design for seismic applications.